Measurement of Li diffusion in porous carbon by neutron depth profiling. Issue 9 (3rd October 2018) - Ceccio, G.; Cannavò, A.; Horak, P.; Torrisi, A.; Tomandl, I.; Hnatowicz, V.; Tsai, H.S.; Vacik, J.
ABSTRACT: Diffusion of Li in porous carbon material has been studied using a nondestructive neutron depth profiling technique. It has been acknowledged that carbon-based materials are good candidates for electrodes in lithium-ion batteries. It is because they exhibit a high ability to effectively release Li ions during charging and discharging processes. The Li diffusion was studied in porous carbon material with several annealing cycles. The produced data were useful for the determination of relative straight porosity level and diffusion coefficient, which result to be between 5.13E-11 cm 2 /s and 5.56E-11 cm 2 /s, that agree with the literature but obtained with a technique that does not alter the sample during the analysis.